Fibroblast growth factor 18 attenuates liver fibrosis and HSCs activation via the SMO-LATS1-YAP pathway. (April 2022) - Tong, Gaozan; Chen, Xixi; Lee, Jongsuk; Fan, Junfu; Li, Santie; Zhu, Kunxuan; Hu, Zijing; Mei, Lin; Sui, Yanru; Dong, Yonggan; Chen, Rui; Jin, Zhouxiang; et al.
Abstract: Liver fibrosis, which is characterized by excessive accumulation of extracellular matrix (ECM) primarily produced by hepatic stellate cells (HSCs), can eventually lead to cirrhosis. Fibroblast growth factor 18 (FGF18) mediates various biological activities. However, the precise role of FGF18 in the pathological process of liver fibrosis and the underlying mechanisms have not been elucidated. In this study, we found that FGF18 was markedly upregulated in carbon tetrachloride (CCl4 )-induced fibrotic mouse liver tissues and transforming growth factor β (TGF-β) stimulated LX-2 cells. Furthermore, our studies demonstrated that overexpression of FGF18 in the liver significantly alleviated CCl4 -induced fibrosis and inhibited the activation of HSCs, while exacerbated by HSC-specific deletion of FGF18. Mechanistically, FGF18 treatment dramatically activated Hippo signaling pathway by suppressing smoothened (SMO) both in vivo and in vitro. Moreover, the interaction between SMO and LATS1 was crucial for the FGF18 induced protective effects. In conclusion, these results indicated that FGF18 attenuates liver fibrosis at least partially via the SMO-LATS1-YAP signaling pathway and therefore may be a potential therapeutic target for liver fibrosis. Graphical Abstract: ga1 Highlights: The protective effects of FGF18 on liver fibrosis mainly attributed to alleviating the activation of hepatic stellate cells. Inhibition of hepatic stellate cells activation depends on Hippo signaling pathway. FGF18 activated Hippo signaling pathway via SMO/LATS1/YAP pathway.